Comment les paysans du corridor forestier de Fianarantsoa (Madagascar) dessinent-ils leur territoire ? Des cartes individuelles pour confronter les points de vue - Dominique Hervé; Jean-Hyacinthe Ramaroson; Andry Randrianarison; Florence Le Ber (Cybergeo)
Currently, in Madagascar, GIS maps are being increasingly produced and used by non-governmental organizations, regarding conservation local contracts. These maps are used by policy makers to determine forest enclosures and to support local development. However, farmers are poorly involved in the map building process and have difficulty to link the maps to their territory. Thus, the goal of our research work is to know how to build a map that everyone can understand. We therefore rely on an empirical approach, based on the methods of participative cartography. First, we want to know how each farmer draws his territory on a blank sheet of paper, and comments his drawing, and second how he does read and correct graphical diagrams, maps, aerial photos and satellite images of this territory. The aim is twofold, first, understanding how maps are viewed by farmers, and second, building a methodological approach to gather the points of view expressed in individual maps drawn by farmers on the same territory. Empirical observations from this survey are presented and discussed, focusing on how Madagascar peasants represent their territory.